Informal economy, institutional quality, and socioeconomic conditions in African countries - Osinubi, Tolulope; Simatele, Munacinga (Universitas Islam Indonesia, 2025)
Purpose — This paper examines the impact of the informal economy and institutional quality on socioeconomic conditions in 35 African countries from 2000 to 2022.Methods — The study employs Driscoll-Kraay, Fully Modified Ordinary Least Squares, Method of Moments Quantile Regression, Dynamic Panel Threshold, and Dumitrescu-Hurlin (D-H) Granger non-causality techniques.Findings — The findings indicate that the informal economy significantly worsens socioeconomic conditions, whereas stronger institutional quality, evident in factors such as government stability and corruption control, enhances these outcomes. A critical institutional quality threshold of 5.282 is established, suggesting that countries with institutional quality above this level experience substantial improvements in socioeconomic conditions. Unidirectional causality from the informal economy to socioeconomic conditions and a bidirectional relationship between institutional quality and socioeconomic outcomes are also noted.Implication — Enhancing institutional quality is essential for promoting economic development and improving overall well-being in African and similar countries. Addressing institutional weaknesses could enable these countries to exceed the quality threshold and achieve better socioeconomic outcomes.Originality — This research differs from previous ones by investigating the effects of both informality and institutional quality within a threshold framework on socioeconomic situations in African countries. Furthermore, it includes a socioeconomic conditions index that combines three subcomponents: poverty, unemployment, and consumer confidence. Additionally, the study employs various measures of institutional quality to explore their differing impacts on socioeconomic conditions.